resale of goods (self-help and emergency sales) in the Convention on International Sale of Goods (1980) and Iranian law with emphasis transportation laws - Meysam Akbari; Hani Hajian (پژوهشنامه حقوق تطبیقی, 2021)
After the sale, the seller is obliged to deliver the goods, and also in the event that the sale is dissolved for any reason and the goods are in the hands of the buyer, he is obliged to return the goods; But if the other party refuses to receive the goods, in Iranian law, the solution that has been considered is to refer to the ruler to oblige the owner of the goods to receive. If the owner of the goods is not required to do so, the only thing that happens is the change of iodine to a safe deposit. In some legal systems, the solution is to resell the goods. One of the most important legal texts in this regard is the Convention on the International Sale of Goods. The study of the possibility of replay in Iranian law is the main question of this research, which has been addressed in a descriptive-analytical manner and with library tools. From the available data, it has been obtained that, firstly, in transportation contracts in Iranian law, this issue has been explicitly accepted without any shortcomings. Secondly, regarding compulsory resale, it is a matter of common sense that the trustee should resell.